The diffusion of the teacher-artist concept in Brazil: reflections on Art as Education in the contemporary context (Revista Apotheke, 2025)
This article discusses the diffusion of the concept of the teacher-artist in Brazil, highlighting its importance in defending art as education. The justification lies in the growing appreciation of the interconnections between art and education, particularly in light of contemporary methodological and curricular transformations that demand more creative and collaborative approaches. Based on a comprehensive literature review on the subject, academic sources encompassing theses, dissertations, books, and articles were analyzed to conduct a survey of the various terminologies that permeate these practices within the national context. The adopted methodology is qualitative in nature and includes the categorization of theoretical and practical contributions surrounding the artist-teacher and its variations. The conclusions indicate that, although the concept is still in the process of consolidation in Brazil, its diffusion has been broad and dynamic, playing a significant role in promoting more inclusive, critical, and sensitive educational practices.
Keywords: Teacher-Artist; Educational Turn; Art-Education; Contemporary Art